2016
DOI: 10.21010/ajtcam.v14i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combretum Hereroense and Canthium Mundianum Water Extracts on Production and Expression of Interleukin-4

Abstract: Background: Combretum hereroense and Canthium mundianum are two plants commonly used by traditional healers in the Northern region of Limpopo, South Africa for the treatment of diarrhea and inflammation. In the present study, the effects of their water extracts on the production and expression of interleukin-4 by peripheral blood mononuclear cells (PBMC'S) from HIV positive and negative individuals was evaluated. Materials and methods: Blood samples were collected from both HIV positive and HIV negative volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, Gholamnezhad et al (2015) showed that Nigella sativa stimulated the production of IL4 in rats. The aqueous extracts of Combretum hereroense and Canthium mundianum leaves induced the production of IL-4 by the human peripheral blood mononuclear cells in vitro (Samie and Madzie, 2016). One the other hand, a study on the immunomodulatory effects of the Aloe vera peel extract in splenocyte cultures showed that this extract did not Kwon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gholamnezhad et al (2015) showed that Nigella sativa stimulated the production of IL4 in rats. The aqueous extracts of Combretum hereroense and Canthium mundianum leaves induced the production of IL-4 by the human peripheral blood mononuclear cells in vitro (Samie and Madzie, 2016). One the other hand, a study on the immunomodulatory effects of the Aloe vera peel extract in splenocyte cultures showed that this extract did not Kwon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%